Saving Behavior Factors among Working Students in Kathmandu Valley Amid the COVID-19 Pandemic - Gyawali, Samjhana; Danuwar, Ranjana Kumari; Devkota, Niranjan; Dhakal, Ajaya (Journal of Innovation in Academia, 2024)
In recent times, the financial landscape of Kathmandu Valley has witnessed a surge in the number of working students who balance their educational pursuits with employment commitments. In parallel, the outbreak of the COVID-19 pandemic has introduced unprecedented economic and sociological disruptions, potentially altering the financial habits of individuals. Therefore, the purpose of this study is to explore the saving behavior of working students in Kathmandu Valley, while also investigating whether the pandemic plays a mediating role in this context. To achieve these objectives, explanatory research design is used to analyze the connections and causal effects between the factors of saving behavior among working students in Kathmandu valley. Structural Equation Modeling (SEM) using the Partial Least Square (PLS) version 4.0 is adopted for data analysis. The findings reveal significant support for all the hypotheses proposed in the study. The analysis indicated that the economic factor, sociological factor, psychological factor and Covid 19 have a positive impact on saving behavior among working students. The results also suggest that the utilization of SEM and SMART PLS provides valuable insight into understanding the relationship between various factors. The study has revealed important new information about the complex dynamics of saving behavior in the context of both personal and societal factors. An in-depth analysis of the impact of economic, sociological, and psychological factors on the financial decisions made by working students in the Kathmandu Valley was conducted in this study, with a focus on the COVID-19 pandemic's mediating role.